Investigation of Nanoscopic Dynamics and Potentials by Interferometric Scattering Microscopy - Ortega Arroyo, Jaime; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This thesis offers a unique guide to the development and application of ultrasensitive optical microscopy based on light scattering. Divided into eight chapters, it covers an impressive range of scientific fields, from basic optical physics to molecular biology and synthetic organic chemistry. Especially the detailed information provided on how to design, build and implement an interferometric scattering microscope, as well as the descriptions of all instrumentation, hardware interfacing and image processing necessary to achieve the highest levels of performance, will be of interest to researchers now entering the field.
Introduction -- Non-fluorescent single-molecule approaches to optical microscopy -- Experimental Methods -- Anomalous diffusion due to interleaflet coupling and molecular pinning -- Structural dynamics of myiosin 5a -- All optical label-free detection, imaging and tracking of single proteins -- Single-molecule chemical dynamics: direct observation of physical autocatalysis -- Outlook.
Keywords: Physical chemistry; Chemistry, Organic; Cytology; Atoms; Molecules; Physical Chemistry; Organic Chemistry; Cell Biology; Atomic, Molecular and Chemical Physics